Metabolic Changes and Serum Ghrelin Level in Patients with Psoriasis - Haydar Ucak; Betul Demir; Demet Cicek; Ilker Erden; Suleyman Aydin; Selma Bakar Dertlioglu; Mustafa Arica (Hindawi Limited, 2014)
Background. Serum ghrelin levels may be related to metabolic and clinical changes in patients with psoriasis. Objective. This study was performed to determine the possible effects of serum ghrelin in patients with psoriasis. Methods. The study population consisted of 25 patients with plaque psoriasis. The patients were questioned with regard to age, gender, age of onset, duration of disease, height, weight, and body mass index (BMI). In addition, fasting blood sugar, triglyceride, cholesterol levels, insulin, and ghrelin levels were measured. Results. The mean serum ghrelin level was 45.41 ± 22.41 in the psoriasis group and 29.92 ± 14.65 in the healthy control group. Serum ghrelin level was significantly higher in the psoriasis group compared with the controls (P=0.01). The mean ghrelin level in patients with a lower PASI score was significantly higher than in those with a higher PASI score (P=0.02). Conclusion. The present study was performed to determine the effects of ghrelin in psoriasis patients. We found a negative correlation between severity of psoriasis and ghrelin level. Larger and especially experimental studies focusing on correlation of immune system-ghrelin levels and severity of psoriasis may be valuable to clarify the etiopathogenesis of the disease.